ASSOCIATION BETWEEN TIMI RISK SCORE AND SEVERITY OF CAD IN NON-STEMI CASES - NIAZI, GZK; BUKHARI, SN; ADNAN, F; SHABBIR, MF (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to evaluate the relationship between TIMI risk score and the extent of coronary artery disease in non-STEMI patients. A descriptive prospective study was conducted in the Department of Cardiology of Chaudhary Pervez Elahi Institute of Cardiology, Multan, from 3rd June 2021-3rd June 2022. 237 patients admitted with NSTEMI within 7 days of admission were included. Baseline demographic characteristics were noted in a performed performance. The TIMI score for all patients was calculated. All patients underwent coronary angiography and the Gensini score was calculated. Average patients’ age was 54.44±9.10 years. The mean genuine score was 37.17±5.62, and the TIMI score was 3.93±1.42. There were 162 (68.35%) male and 75 (31.65%) female patients. Diabetes was found in 83 (35.02%) and hypertension in 124 (52.32%) patients. Family history of CAD was found in 54 (22.78%) patients, and hypercholesterolemia in 57 (22.05%) patients. TIMI score significantly correlated with Gensini score with a correlation coefficient (r) of 0.50 and p-value <0.0001. It is concluded that in NSTEMI patients, clinical risk stratification as determined by TIMI risk score is associated with the determined extent of the disease via the Gensini score.